Strategi Guru Akidah Akhlak Berbasis I2M3 dan Inkuiri: I2M3 and Inquiry Strategies in Akidah Akhlak Learning - syahri, melani purnama; s, Zulkarnain; Riadi, Dayun (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Learning processes in Islamic education require strategies that promote student engagement and critical thinking development within meaningful classroom interactions. Specific Background: The I2M3 learning approach interactive, inspirational, enjoyable, challenging, and motivating has been introduced in Akidah Akhlak education to support active participation and contextual understanding among students. Knowledge Gap: However, classroom practices in Akidah Akhlak often remain conventional, resulting in limited student involvement and underdeveloped critical thinking skills despite initial implementation of innovative approaches. Aims: This study aims to describe teacher strategies in implementing I2M3-based inquiry learning and examine their role in fostering student activeness and critical thinking skills at SMP Insan Kamil Islamic School Bengkulu. Results: Using a descriptive qualitative method through observation, interviews, and documentation, the findings show that teachers systematically apply inquiry-based strategies aligned with I2M3 principles, including interactive discussions, contextual learning, collaborative projects, and reflective activities. These strategies increase student participation, encourage analytical thinking, and support meaningful engagement with moral and religious concepts. Novelty: The study highlights the integration of inquiry strategies within the I2M3 framework as a structured approach in Akidah Akhlak learning. Implications: The findings suggest that such strategies contribute to developing active, critical, and character-oriented learners, while also identifying challenges related to student diversity, time constraints, and learning resources that require adaptive teaching practices. Highlights• Inquiry-based classroom practices structured sequential student engagement• Contextual moral case analysis strengthened reasoning processes• Collaborative activities supported participation across diverse learner abilities KeywordsTeacher Strategy; I2M3 Learning; Inquiry Learning; Active Learning; Critical Thinking